Performance validation of the heat extraction performance by the natural ventilation with a board-coupled shaft in a deep buried tunnel. (January 2022) - Cong, Haiyong; Bi, Mingshu; Ren, Jingjie; Li, Bei; Bi, Yubo; Gao, Wei
Highlights: The heat extraction performance of the BCSs in a deeper buried tunnel is explored. BCS is effective and has stable heat extraction performance in deeper buried tunnels. Smoke layer thickness in the one-dimensional flow region depends only on the position. Dimensionless smoke layer thickness in the one-dimensional flow region ( h int H ) is deduced. Dimensionless heat extraction rate ( q s ∗ ) and temperature difference ( Δ T s ∗ ) are deduced. Abstract: Experiments were conducted in a 1/20 scale model tunnel, a higher shaft (5 times the tunnel height) was applied to model the shaft in a deep buried tunnel. Researches have validated that the board-coupled shaft can efficiently eliminate the plug-holing phenomenon and improve the smoke and heat extraction performance when the board-coupled shaft is suitably applied in a shallow buried tunnel. The purpose of this paper is to explore whether the board-coupled shaft (BCS) is effective and has stable heat extraction performance in deep buried tunnels. The influence of heat release rate (HRR) and board location on the heat extraction performance was investigated. The experimental results show that the BCS is effective and has stable heat extraction performance for the deep buried tunnels applied in this study. Also, an analytical solution for predicting the dimensionless smoke layer thickness in the one-dimensional flow region was developed, and it can be found that the dimensionless smoke layer thickness in the one-dimensional flow region depends only on the longitudinal position and doesn't rely on the HRR. Furthermore, based on the general condition that the first shaft cannot extract the entirety of the smoke, two empirical correlations were derived for predicting the dimensionless temperature difference (Δ T s ∗ ) and the dimensionless heat extraction rate ( q s ∗ ) in the BCS under different HRRs and board locations. These studies may contribute positive significance for promoting the application of natural ventilation with vertical shafts in deep buried tunnels.